Scalable IP lookup for Internet routers - Taylor, D.E.; Turner, J.S.; Lockwood, J.W.; Sproull, T.S.; Parlour, D.B. (IEEE journal on selected areas in communications, 2003)
Internet protocol (IP) address lookup is a central processing function of Internet routers. While a wide range of solutions to this problem have been devised, very few simultaneously achieve high lookup rates, good update performance, high memory efficiency, and low hardware cost. High performance solutions using content addressable memory devices are a popular but high-cost solution, particularly when applied to large databases. We present an efficient hardware implementation of a previously unpublished IP address lookup architecture, invented by Eatherton and Dittia (see M.S. thesis, Washington Univ., St. Louis, MO, 1998). Our experimental implementation uses a single commodity synchronous random access memory chip and less than 10% of the logic resources of a commercial configurable logic device, operating at 100 MHz. With these quite modest resources, it can perform over 9 million lookups/s, while simultaneously processing thousands of updates/s, on databases with over 100000 entries. The lookup structure requires 6.3 bytes per address prefix: less than half that required by other methods. The architecture allows performance to be scaled up by using parallel fast IP lookup (FIPL) engines, which interleave accesses to a common memory interface. This architecture allows performance to scale up directly with available memory bandwidth. We describe the tree bitmap algorithm, our implementation of it in a dynamically extensible gigabit router being developed at Washington University in Saint Louis, and the results of performance experiments designed to assess its performance under realistic operating conditions.